PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN YANG TERDAFTAR di BURSA EFEK INDONESIA - Galuh Nur Fitri B.S; Bambang Subroto (Jurnal Ilmiah Mahasiswa FEB, 2012)
This study examined the effect of Good Corporate Governance (GCG) to disclosure of Corporate Social Responsibility (CSR). Board size, frequency of board meetings, board independence, audit committee size, frequency of meetings of the audit committee, the audit committee competence, managerial ownership, institutional ownership, foreign ownership, and the concentrated ownership is a proxy of corporate governance mechanisms. Tests were conducted at 65 public companies in Indonesia Stock Exchange that perform social responsibility disclosure in the Annual Report reporting period in 2011. These results indicate that the mechanisms of good corporate governance which affect the disclosure of Corporate Social Responsibility is concentrated stock ownership factor. As for the other factors such as board size, frequency of board meetings, board independence, audit committee size, frequency of audit committee meetings, audit committee competence, managerial ownership, institutional ownership and foreign ownership are not significantly influence on the CSR disclosure companies in Indonesia. The implications of this research for policymakers warned that should the implementation and reporting obligations of social responsibility by supporting policies are also followed. Another important implication of the need for improvement of the system of corporate governance and reporting in accordance with the implementation of social accountability. Keywords: Corporate Social Responsibility (CSR), Characteristics of Good Corporate Governance (GCG), the Board, Audit Committee, Shareholding Structure.